1983
DOI: 10.1093/ajcn/37.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ascorbic acid supplementation on copper status in young adult men

Abstract: The influence of ascorbic acid supplementation on the copper status of young adult men was investigated. Subjects consuming self-selected diets took 500 mg of ascorbic acid with each meal (1500 mg/day) for 64 days. Blood samples were obtained at 0, 28, 52, and 64 days in order to determine serum copper and serum ceruloplasmin. Each subject thus served as his own control. Analyses were repeated 20 days after the ascorbic acid supplement was terminated. Serum ceruloplasmin activity was significantly reduced (p l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 40 publications
1
19
1
Order By: Relevance
“…Previous studies on laboratory animals and young humans reported that with high dose of vitamin C intake decreased the levels of serum ceruloplasmin. 24,25 Findings of this study is not in agreement with the previous study ; which may be due to the difference in the dosage levels. In the present study the dosage used was 20mg/kg b.w.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous studies on laboratory animals and young humans reported that with high dose of vitamin C intake decreased the levels of serum ceruloplasmin. 24,25 Findings of this study is not in agreement with the previous study ; which may be due to the difference in the dosage levels. In the present study the dosage used was 20mg/kg b.w.…”
Section: Discussioncontrasting
confidence: 84%
“…Apart from some genetic disorders, leukemias, and lymphoproliferative disorders (36), the only known cause of reduced ESOD activity is copper depletion, and in studies of copperdepleted adults (1 1, 12) or those receiving zinc supplements (10, 13) a reduction of ESOD activity was the earliest indicator of disturbed copper metabolism. Although high doses of ascorbic acid can alter the metabolism of copper in rats (37) and adult men (38,39), the doses of ascorbate used in this study were similar in all treatment groups. Similarly, solids contributed only a small amount to the dietary intake of 15 infants and would take longer than 2 wk to have any effect on ESOD activity.…”
Section: Discussionmentioning
confidence: 79%
“…Its interaction with the copper I1 (cupric) ion is well known, but the in vivo biological consequences of this interaction are less well understood. Previous studies have explored some aspects of this interaction in guinea-pigs (Hitier, 1976;Milne & Omaye, 1980;Smith & Bidlack, 1980;Kassouny et al 1985;DiSilvestro, 1986;Pekiner & Nebioglu, 1994); in rats (Van Campen & Gross, 1968;Johnson & Murphy, 1988;van den Berg et al 1994); in rabbits (Hunt & Carlton, 1965); in chicks (Starcher et al 1964;Carlton & Henderson, 1965;Hill & Starcher, 1965;DiSilvestro & Harris, 1981); in monkeys (Milne et al 1981) and in human subjects (Finley & Cerklewski, 1983;Jacob et al 1987;Milne et al 1988;Pekiner & Nebioglu, 1994). There have also been studies in cultured cells (Harris & Percival, 1991 .…”
mentioning
confidence: 99%